Capital market in a planned economy - National Council of Applied Economic Research (New Delhi India : V.G.K. Thathachary, Administrative officer, National Council of applied Economic Research, 1966)
The study has analysed the various factors that have brought about the sluggishness of the capital market. It has shown that apart from inhibitive fiscal policy, there are many others responsible for the situation
osc 03/08/2018
Loans
Keywords: Corporations